Evaluation of coupling and coordination, obstacle diagnosis, and optimization pathways of medical–preventive integration in primary healthcare institutions in Hebei Province from 2017 to 2024 - Botao Yang; Kexin Li; Zike Zhao; Zhihui Cao (PLoS ONE, 2026)
Medical–prevention integration constitutes a core governance strategy for advancing the Healthy China initiative, with primary healthcare institutions serving as the foundational delivery platforms for its implementation. To systematically evaluate the development level, spatiotemporal evolution, and key constraining factors of medical–prevention integration at the primary level, this study takes all township health centers and community health service centers in Hebei Province as the research sample. Drawing on panel data from the Hebei Health Statistical Yearbook covering 2017–2024, an evaluation index system for the coupling and coordinated development of primary medical services and public health services was constructed and authoritatively validated using a modified Delphi method. Indicator weights were determined through the entropy method, and an integrated quantitative analytical framework was employed, incorporating the coupling coordination degree model, the relative development model, and the obstacle degree model. The results indicate that primary medical–prevention integration in Hebei Province exhibits a typical pattern of “high coupling but low coordination”. Although medical and public health services have established a relatively stable institutional linkage, their overall coordinated development remains at a persistently low level, with medical services generally outperforming public health services. Township health centers demonstrate significantly higher composite development levels and coupling coordination degrees than community health service centers, forming a pronounced urban–rural dual structure in primary-level medical–prevention integration. Furthermore, substantial heterogeneity exists between the two types of institutions in terms of relative development structures and core obstacle factors. Lagging public health service capacity, along with misaligned financing and incentive mechanisms, constitutes the principal bottleneck constraining high-quality development of medical–prevention integration. By uncovering the underlying structural and institutional tensions within primary-level medical–prevention integration, this study provides robust empirical evidence and policy-relevant insights for optimizing integration strategies and advancing the construction of an integrated healthcare delivery system in Hebei Province and other comparable regions in China.